The Influence of Lifestyle and Brand Image on Purchasing Decisions for Mundo Products with Purchase Intention as an Intervening Variable - Pratama Perangin-angin, Muhammad Farid; Hommy Dorthy Ellyany Sinaga; Petrus Loo (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2023)
The textile industry in Indonesia has great potential with various types of raw materials, including cotton, silk, rattan, and polyester. An integrated supply chain is the key to success in this industry, which is currently experiencing positive growth. Socks are an important textile product and have become part of the lifestyle, especially in the digital era. This study aims to understand the effect of lifestyle and brand image in the digitalization era on purchasing decisions for Mundo socks products through purchase intention as an intervening variable. This research uses descriptive quantitative methods and involves 250 retail stores spread across the city of Medan. The research sample size was determined by the Slovin method with an error rate of 5% resulting in 154 respondents. data was collected with various research instruments, literature studies and research questionnaires. The results showed that Lifestyle and Brand Image and Purchase Intention as intervening variables had a partial and simultaneous effect on Purchasing Decisions at PT. Jumbo Niaga Lestari. And Lifestyle is the most dominant variable influencing Purchasing Decisions at PT. Jumbo Niaga Lestari.